Modifikasi Rumah Kolonial Untuk Usaha Mandiri Di Semarang - Antonius Ardiyanto; Rudyanto Susilo; Valentinus Suroto; Hudi Prawoto (Tesa Arsitektur, 2017)
ABSTRACT Semarang city there are many residential buildings built in the colonial period. Colonial dwelling house is spread in various areas of Semarang city, such as in the residential area of Candi in the upper city. This area in the colonial period is an elite residential area with a fairly large building area of about 1000 m2 which is planned as a water absorption area for water reserves in the lower cities. Some colonial residential buildings today have been converted to function as a place of business such as café or restaurant. The transfer function of the residential building into a place of business is done by modifying the existing space adjusted for the space character for the type of business. The purpose of this study is to know how the modification of the colonial house, especially in the spatial in maximizing space as a place of independent business. The research was conducted by descriptive method, with the sample taken by purposive. The results showed that the modification of the colonial house to independent business is manifested in the change of function of the living room into a space of business which is adapted to the specificity of its business activity. In addition, the addition and alteration of building materials is used to emphasize the main functions of the business. While in general plan of building of main house stay tends not change. Keywords : colonial house, modification, independent bussiness ABSTRAK Kota Semarang terdapat banyak bangunan rumah tinggal yang dibangun pada masa kolonial. Rumah tinggal kolonial tersebut tersebar diberbagai wilayah kota Semarang, diantaranya di kawasan permukiman Candi di kota atas. Kawasan ini pada masa kolonial merupakan kawasan permukiman elit dengan lahan bangunan yang cukup luas sekitar 1000 m2 yang direncanakan sebagai daerah peresapan air untuk cadangan air di kota bawah. Beberapa bangunan rumah tinggal kolonial saat ini telah dialih fungsikan sebagai tempat usaha seperti café atau restoran. Alih fungsi bangunan rumah tinggal menjadi tempat usaha dilakukan dengan memodifikasi ruang yang ada disesuaikan untuk karakter ruang untuk jenis usahanya. Tujuan dari studi ini adalah mengetahui bagaimana bentuk modifikasi rumah kolonial khususnya dalam tata ruang dalalamnya dalam memaksimalkan ruang sebagai tempat usaha mandiri. Penelitian dilakukan dengan metoda deskriptif, dengan sampel diambil secara purposive. Hasil penelitian menunjukan bahwa modifikasi rumah kolonial untuk usaha mandiri diwujudkan dalam perubahan fungsi ruang – ruang tempat tinggal menjadi ruang tempat usaha yang disesuaikan dengan kekhususan kegitan usahanya. Selain itu, penambahan dan perubahan material bangunan digunakan untuk memberi penekanan pada fungsi utama pada kegiatan usaha tersebut. Sedangkan secara umum denah bangunan rumah tinggal utama cenderung tidak berubah. Kata Kunci : Kolonial, Usaha, Modifikasi